Pengaruh Tarif Pajak dan Probabilitas Audit terhadap Kepatuhan Pajak Penghasilan (Studi Eksperimen Laboratorium) - Kalangi, Lintje (Universitas Sam Ratulangi, 2014)
The objective of this research is to analyze the effect of tax rates, and the probability of audit on individual income tax compliance.This research is an explanatory research, which done through laboratory experiment, to explain the casual relationships (causality) between variables. Participants of this experiment consit of 30 students Master of Accounting and Accounting Professional Program at Faculty of Economics, Sam Ratulangi University, Manado. The model analysis was of the research using Normal Censored Tobit ).The results indicate that: (1) tax rate has positive effect on tax compliance behavior. (2) probability of audit has positive effect on compliance tax and changes in probability of audit level has different effect on compliance tax.